Adapting Mintzberg’s organizational theory to DeSci: the decentralized science pyramid framework - Weidener, Lukas; Greilich, Konrad; Melnykowycz, Mark (Frontiers in Blockchain, 2024)
To solve some of the challenges of traditional science, such as restricted access to funding, centralized governance, and siloed knowledge dissemination, decentralized science (DeSci) has emerged as a transformative approach facilitated by blockchain technology, Decentralized Autonomous Organizations (DAOs), and Web3. However, the emerging field of DeSci, faces several challenges, such as the absence of an organizational framework to describe its inherent complexities. This study introduces the Decentralized Science Pyramid Framework (DSPF), an innovative adaptation of Mintzberg’s organizational structure, adapted to the unique demands and properties of DeSci. The DSPF delineates a structured model for DeSci projects that integrates technology, governance, community engagement, and application within a decentralized context. Through the introduction of the DSPF, this research highlights the operational dynamics of DeSci, focusing on the practical application of Mintzberg’s theories to address real-world scientific challenges. The case study of VitaDAO, a decentralized autonomous organization exemplifying the core principles of DeSci, demonstrates the practical applicability of the DSPF. This study not only advances the academic discourse on DeSci but also offers practical insights for practitioners, innovators, and policymakers, marking a substantial step toward realizing the full potential of decentralized science.